Kerangka Konsep Pengembangan Kurikulum Berbasis Multiple Intelligence pada Pendidikan Anak Usia Dini - Shofa, Mila Faila (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
The aims of this article are to (1) describes the concept of Multiple Intelligence-based curriculum development in Early Childhood Education, (2) describes the implications of curriculum-based learning at the Multiple Intelligence in Early Childhood Education. Data acquisition method of this article is through literature and empirical experience of the author. The results of this article explains that exposure to develop the Multiple Intelligence-based curriculum, teachers and school curriculum development team can put the idea of Multiple Intelligence manner. Multiple Intelligence curriculum can be reflected with some learning approaches, including approaches based learning center. Multiple Intelligence curriculum can be organized with the 2013 early childhood curriculum where the curriculum structure is the organization of core competencies, basic competencies, and learning the charge with each of multiple intelligences. Implications of Multiple Intelligence learning curriculum through three stages namely planning, implementation, and evaluation. Learning plan includes lesson plans based on Multiple Intelligence Weekly and Daily Lesson Plan-Based Multiple Intelligence. The learning center is implemented through activities in accordance with the linguistic intelligence center, musical center, visual-spatial center, kinestetic center, logical-mathematical center, center intrapersonal, interpersonal center, naturalist center, and existentialist center. Rating is based on the development of students achievement indicators for each intelligence at every age.